1998
DOI: 10.1046/j.1365-294x.1998.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Local genetic structure in red grouse (Lagopus lagopus scoticus): evidence from microsatellite DNA markers

Abstract: Allelic variation at seven hypervariable tri- and tetranucleotide microsatellite loci was used to determine levels of population differentiation between 14 populations of red grouse (Lagopus lagopus scoticus) in northeast Scotland, UK. Despite the potential for long-distance dispersal in grouse, and a semicontinuous habitat, significant population divergence was observed (mean RST = 0.153; P < 0.01) and an isolation-by-distance effect detected (Mantel test: P < 0.001). Examination of the spatial trend in princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 41 publications
9
143
1
3
Order By: Relevance
“…The mean estimated dispersal distance for Swedish hazel grouse (Bonasa bonasia) was 1514m (Sahlsten et al 2008) and for English black grouse the estimated mean dispersal distance during early spring was 5.8 km and during fall 10.5km (Warren and Baines 2002). In comparison the estimated dispersal distance of the Irish red grouse of 5.6 km is not unreasonable and together with evidence of dispersal limitations (Piertney et al 1998), an indication that natural dispersal between the putative remaining population fragments is unlikely.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The mean estimated dispersal distance for Swedish hazel grouse (Bonasa bonasia) was 1514m (Sahlsten et al 2008) and for English black grouse the estimated mean dispersal distance during early spring was 5.8 km and during fall 10.5km (Warren and Baines 2002). In comparison the estimated dispersal distance of the Irish red grouse of 5.6 km is not unreasonable and together with evidence of dispersal limitations (Piertney et al 1998), an indication that natural dispersal between the putative remaining population fragments is unlikely.…”
Section: Discussionmentioning
confidence: 81%
“…An additional 28 samples from Scotland were obtained from birds collected in Aberdeenshire (Piertney et al 1998). All samples had an associated sampling reference that varied in accuracy from known grid reference sampling location, to the scale of the nearest town (<10 kms).…”
Section: Sampling and Study Areasmentioning
confidence: 99%
“…Subsequent analysis of the data has revealed periodic travelling waves moving across the domain at a speed of 2-3 km/year (Moss et al, 2000). One edge of the study area is bordered by farmland, which is a very hostile environment for red grouse (Piertney et al, 1998). Therefore, a Robin condition is appropriate at this boundary and could be responsible for the observed periodic travelling waves.…”
Section: Discussionmentioning
confidence: 94%
“…However, it may also arise without physical barriers when behaviours such as territoriality, site fidelity or natal philopatry prevent the spatial mixing of genes (Sugg et al, 1996). In red grouse Lagopus lagopus scoticus, for example, Piertney et al, 1998 reported significant genetic divergence among 14 populations separated by 1 to 50 km, and suggested that territoriality and natal philopatry were the main factors promoting such genetic differentiation. Similarly, genetic structure at a fine geographic scale is common in organisms with particular social systems (for example eusocial insects, cooperatively breeding birds and mammals) through the effects of dispersal patterns on kinship; such structure is often sex-specific when the sexes differ in their dispersal strategy (Sugg et al, 1996;Dobson, 1998;Storz, 1999;Ross, 2001).…”
Section: Introductionmentioning
confidence: 99%